Effects of breed and dietary protein supplementation on the responses to gastro intestinal nematode infections in Ethiopian sheep - Haile, Aynalem; Tembely, S.; Anindo, D.O.; Mukasa-Mugerwa, E.; Rege, J.E.O.; Yami, A.; Baker, R.L. (Elsevier, 2002)
The effects of breed and dietary protein supplementation on the development of resistance and resilience to gastrointestinal nematode parasites (endoparasites) were examined in artificially infected Horro and Menz lambs from 4 to 12 months of age. The factorial design involved two breeds, two infection treatments (infected vs non-infected) and three dietary protein treatments (hay and wheat bran (basal diet), hay plus molasses urea block (MUB), hay plus cotton seed cake (CSC)). At the start of the study, 152 weaner lambs (103 Menz and 49 Horro) were assigned to the 12 treatment combinations each in a separate pen. Endoparasite challenge involved three infection periods (primary, secondary and tertiary) each separated by an anthelmintic treatment. The first two infections were with Haemonchus contortus, while the third infection was a mixed infection of H. contortus, Longistrongylus elongata and Trichostrongylus colubriformis. During the entire study, infected lambs gained significantly less weight and had a lower blood packed cell volume (PCV) than the non-infected lambs. Protein supplementation of lambs with CSC resulted in lower faecal egg counts (FEC) and higher PCV and growth rates than lambs fed the basal diet. In the first two infection periods there was no significant effect of infections in lambs supplemented with MUB, probably due to low intake of MUB. In the tertiary infection period MUB was fed ad libitum which resulted in MUB-supplemented lambs having significantly higher PCV than lambs on the basal diet, with CSC-supplemented lambs intermediate. During the primary infection, naive Horro lambs had a significantly lower FEC than Menz lambs, but there was no significant breed difference for PCV In the secondary infection period there was no significant breed difference for FEC or PCV in infected lambs. However, during the tertiary infection, while there was no significant breed difference for FEC, the Menz had a significantly higher PCV than Horro irrespective of infection status. At the end of the tertiary infection, the Menz lambs (n = 26) had significantly lower adult worm burdens for H. contortus and L. elongata than Horro lambs (n = 18), but there was no significant difference between the breeds for T. colubriformis worm burdens. Both the worm count and PCV data suggest that Menz lambs acquire the ability to resist and tolerate endoparasite infections better than the Horro lambs.